THE EFFECT OF WORDWALL MEDIA GAME ON VOCABULARY DEVELOPMENT: A QUASI-EXPERIMENTAL STUDY - Yanti Kristina Sinaga; Novia Aryani; Herman Herman; Fahrus Zaman Fadhly; Rahmawati Rahmawati; Nabil Al-Awawdeh (English Review: Journal of English Education, 2025)
This study examines the effectiveness of WordWall, a digital game-based learning platform, in improving students’ English vocabulary achievement. Conducted at SMP Negeri 4 Kota Pematangsiantar during the 2025/2026 academic year, the research involved 62 seventh-grade students divided into two groups: an experimental group taught using WordWall and a control group taught through traditional textbook-based instruction. Employing a quasi-experimental design with pre-test and post-test procedures for both groups, the study found a notable increase in the vocabulary scores of the experimental group compared to the control group. The experimental group’s mean post-test score (85.06) surpassed the school’s minimum mastery criterion (KKM) of 72, while the control group’s mean score was 71.6. Results from paired and independent sample t-tests indicated a significant difference (p < 0.05) between the two groups, validating the positive influence of WordWall on vocabulary acquisition. Moreover, students exposed to WordWall showed improved understanding and retention of word formation, such as recognizing different word classes (nouns, verbs, etc.). These findings highlight that incorporating digital game-based tools like WordWall can enhance both student engagement and learning outcomes. The study concludes that WordWall effectively supports vocabulary development while promoting a more interactive and learner-centered classroom environment, and recommends its adoption by teachers to overcome vocabulary learning challenges in English education.